ANALISIS TINGKAT KESEHATAN KOPERASI KREDIT â€œKOSAYUâ€ PERIODE 2014-2016 BERDASARKAN PERATURAN DEPUTI BIDANG PENGAWASAN KEMENTERIAN KOPERASI DAN USAHA KECIL DAN MENENGAH REPUBLIK INDONESIA NOMOR: 06/PER/DEP.6/IV/2016 - Sari, Putri Sekti Purnama (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Â The study tries to determine the health level of â€œKosayuâ€ Credit Cooperatives during the period of 2014-2016 viewed from its financial and management aspects. This descriptive quantitative research applies a case-study towards â€œKosayuâ€ Credit Cooperatives. The data analysis are derived from the Regulation of the Deputy of Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia, Number: 06/Per/ Dep.6/IV/2016 concerning the Guidelines for Health Assessment of the Savings and Loans Cooperatives and the Savings and Loans Unit, which covers seven aspects: capital, productive asset quality, management, efficiency, liquidity, independence and growth, and management.The results of the study show that the health level of â€œKosayuâ€ Credit Cooperatives in 2014 was under the category of